Wide-bandwidth drift-scan pulsar surveys of globular clusters: application to early science observations with FAST. (October 2016) - Zhang, Lei; Hobbs, George; Li, Di; Lorimer, Duncan; Zhang, Jie; Yu, Meng; Yue, You-Ling; Wang, Pei; Pan, Zhi-Chen; Dai, Shi
Abstract: The Five-hundred-meter Aperture Spherical Telescope (FAST) will begin its early-science operations during 2016. Drift-scan pulsar surveys will be carried out during this period using an ultra-wide-band receiver system (covering ∼ 270 to 1620 MHz). We describe a method for accounting for the changes in the telescope beam shape and the pulsar parameters when searching for pulsars over such a wide bandwidth. We applied this method to simulated data sets of pulsars in globular clusters that are visible to FAST and found that a representative observation would have a sensitivity of ∼ 40 μJy. Our results showed that a single drift-scan (lasting less than a minute) is likely to find at least one pulsar for observations of four globular clusters. Repeated observations will increase the likely number of detections. We found that pulsars in ∼16 clusters are likely to be found if the data from 100 drift-scan observations of each cluster are incoherently combined.